Pembuatan Laboratorium Media Berbasis Lingkungan dan Keunggulan Lokal Kudus - Ulya, Himmatul; Ardianti, Sekar Dwi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
The existence of a laboratory in Primary School 4 Karangbener (SD 4 Karangbener) was not used for learning but was converted into a warehouse. Lack of knowledge and skills of teachers and students in utilizing the environment and local superiority of Kudus to develop learning media and Mathematics and Natural sciences games cause a lack of media availability. This causes the teacher to dominate the implementation of learning so that student learning activities become low. The purpose of this mentoring activity is to design a laboratory that is available to be an environmentally based Mathematics and Natural Sciences media laboratory and Kudus local excellence. It aims to improve teacher skills in developing learning media and Mathematics and Natural Sciences games and student learning activities. The method used in this activity is to provide interactive training and mentoring. The results of this activity are that teachers and students can create and use learning media and games for Mathematics and Natural Sciences based on Kuduslocal excellence, teachers can reconstruct laboratory space and can utilize laboratory space through the implementation of Mathematics and Natural Sciences learning.